(3TQM GdQSGdI GdJQTjMjI ddSeQbfOj aj GdGSJYGQGJs - (3GdCSaQGjjfj, GdYUGe, EHQGgje Hf eMeO YQH TGg, J(B945(3g`s ((3eMeO Hf SdjeGfs)
(3ChdgG (B:s
(3jbhdYUGe GdOjf Hf eMeOGdMeO dhGgH GdYWjI Cj cd YWjI Ch GdYWjI GdeYghOI GdJj fRdJ ajgG GdShQI aj JfGSH abQJG GdMeO hGdUdGIs
(3BNQgG (B:s
(3jMVQ Hg GdSGeY ChdG agh GdbQjfI heG ShGg JQTM hdc Cf JLYd GdLejY bQjfI aj ebGe TOI GdGgJeGe HGdEjVGMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 66s
(3eYLe GdeDdajf(B: 1 / 67s
(3cTa GdXfhf(B: 1 / 853s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdHdGZIs